Pregunta
5. Calculate the value of the expression \( 3 x^{2}+4 x-5 \) when \( \begin{array}{lll}\text { a) } x=-1 & \text { b) } x=-2 & \text { c) } x=0\end{array} \)
Ask by Ayala Moran. in South Africa
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
When \( x = -1 \), the expression \( 3x^{2} + 4x - 5 \) equals **-6**.
When \( x = -2 \), the expression equals **-1**.
When \( x = 0 \), the expression equals **-5**.
Solución
Sure, let's evaluate the expression \( 3x^{2} + 4x - 5 \) for each given value of \( x \).
## Expression:
\[ 3x^{2} + 4x - 5 \]
## a) When \( x = -1 \):
1. **Substitute** \( x = -1 \) into the expression:
\[
3(-1)^{2} + 4(-1) - 5
\]
2. **Calculate the exponent**:
\[
(-1)^{2} = 1
\]
So,
\[
3(1) + 4(-1) - 5
\]
3. **Multiply**:
\[
3 \times 1 = 3
\]
\[
4 \times (-1) = -4
\]
Now,
\[
3 - 4 - 5
\]
4. **Add/Subtract**:
\[
3 - 4 = -1
\]
\[
-1 - 5 = -6
\]
**Result**:
\[
3(-1)^{2} + 4(-1) - 5 = -6
\]
---
## b) When \( x = -2 \):
1. **Substitute** \( x = -2 \) into the expression:
\[
3(-2)^{2} + 4(-2) - 5
\]
2. **Calculate the exponent**:
\[
(-2)^{2} = 4
\]
So,
\[
3(4) + 4(-2) - 5
\]
3. **Multiply**:
\[
3 \times 4 = 12
\]
\[
4 \times (-2) = -8
\]
Now,
\[
12 - 8 - 5
\]
4. **Add/Subtract**:
\[
12 - 8 = 4
\]
\[
4 - 5 = -1
\]
**Result**:
\[
3(-2)^{2} + 4(-2) - 5 = -1
\]
---
## c) When \( x = 0 \):
1. **Substitute** \( x = 0 \) into the expression:
\[
3(0)^{2} + 4(0) - 5
\]
2. **Calculate the exponent**:
\[
(0)^{2} = 0
\]
So,
\[
3(0) + 4(0) - 5
\]
3. **Multiply**:
\[
3 \times 0 = 0
\]
\[
4 \times 0 = 0
\]
Now,
\[
0 + 0 - 5
\]
4. **Add/Subtract**:
\[
0 + 0 = 0
\]
\[
0 - 5 = -5
\]
**Result**:
\[
3(0)^{2} + 4(0) - 5 = -5
\]
---
## Summary of Results:
- **a)** When \( x = -1 \), the expression evaluates to **-6**.
- **b)** When \( x = -2 \), the expression evaluates to **-1**.
- **c)** When \( x = 0 \), the expression evaluates to **-5**.
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Mind Expander
To calculate the value of the expression \( 3 x^{2}+4 x-5 \) for the given values of \( x \): a) When \( x = -1 \): \[ 3(-1)^{2}+4(-1)-5 = 3(1) - 4 - 5 = 3 - 4 - 5 = -6 \] b) When \( x = -2 \): \[ 3(-2)^{2}+4(-2)-5 = 3(4) - 8 - 5 = 12 - 8 - 5 = -1 \] c) When \( x = 0 \): \[ 3(0)^{2}+4(0)-5 = 0 + 0 - 5 = -5 \] So, the values are: a) -6, b) -1, c) -5.
preguntas relacionadas
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium